Kontribusi Inovasi Pelayanan Publik terhadap Kepuasan Pelanggan dalam Penerbitan Paspor di Kantor Imigrasi Kelas I Padang - Yersa Novellina Putri; Dasman Lanin (Journal of Education on Social Science (JESS), 2018)
This study aimed to determine the contribution of public service innovation on customer satisfaction in issuing passports at the Office of Immigration Class I Padang. The background of this research was that there were many people complained about the queue for passport request. This study was conducted through a quantitative approach. The population in this study was all Indonesian Citizens (WNI) who had received passport request services from the Office of Immigration Class I Padang from January to June 2018 totaling 16.311. The sample in this study consisted of 390 respondents determined with Slovin Formula and through a proportionate stratified random sampling technique. Data in this study were collected through questionnaires with Likert Scale measurement. The data were analyzed using multiple linear regression tests. The partial test results showed that the novelty dimension (X1), the productive dimension (X2), the impact dimension (X3), and the sustainability dimension (X4) had a significant contribution on customer satisfaction with a significance value of 0,000. While simultaneously public service innovations (consisted of novelty, productive, impact, and sustainability) had a significant contribution on customer satisfaction in issuing passports at the Office of Immigration Class I Padang.